2018
DOI: 10.1038/s41419-018-1103-y
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPβ deletion in oncogenic Ras skin tumors is a synthetic lethal event

Abstract: Therapeutic targeting of specific genetic changes in cancer has proven to be an effective therapy and the concept of synthetic lethality has emerged. CCAAT/enhancer-binding protein-β (C/EBPβ), a basic leucine zipper transcription factor, has important roles in cellular processes including differentiation, inflammation, survival, and energy metabolism. Using a genetically engineered mouse model, we report that the deletion C/EBPβ in pre-existing oncogenic Ha-Ras mouse skin tumors in vivo resulted in rapid tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…Lastly, we focused on those TFs that had been previously linked to RAS signaling (Cebpα, Cebpβ, Cmyb, Evi1, Meis1, The similar expression pattern of Gata3 and miR181a/miR181b, and the presence of regulatory elements in the Mir181ab1 promoter suggested that miR181a1 and miR181b1 could be regulated by Gata3. To substantiate this potential association, further analysis of GATA3 expression was done in immortalized lung epithelial cells expressing Gata2, Gata3, and Foxa2) (51)(52)(53)(54)(55)(56)(57)(58). Quantitative PCR (qPCR) analysis of the TFs revealed upregulation of Gata3 in both mouse lung and pancreatic cancer cell lines after TGF-β treatment for 3 hours ( Figure 9C), while no consistent upregulation in the 2 cell lines was found for the remaining TFs (Supplemental Figure 6, C and D).…”
Section: Resultsmentioning
confidence: 95%
“…Lastly, we focused on those TFs that had been previously linked to RAS signaling (Cebpα, Cebpβ, Cmyb, Evi1, Meis1, The similar expression pattern of Gata3 and miR181a/miR181b, and the presence of regulatory elements in the Mir181ab1 promoter suggested that miR181a1 and miR181b1 could be regulated by Gata3. To substantiate this potential association, further analysis of GATA3 expression was done in immortalized lung epithelial cells expressing Gata2, Gata3, and Foxa2) (51)(52)(53)(54)(55)(56)(57)(58). Quantitative PCR (qPCR) analysis of the TFs revealed upregulation of Gata3 in both mouse lung and pancreatic cancer cell lines after TGF-β treatment for 3 hours ( Figure 9C), while no consistent upregulation in the 2 cell lines was found for the remaining TFs (Supplemental Figure 6, C and D).…”
Section: Resultsmentioning
confidence: 95%
“…Therefore, it is likely a yet undisclosed TGF-β mechanism contributed to the anti-senescent activity of Y-27632. Additional reports of pathways associated with RAS induced senescence in keratinocytes include ID1, 37 CEBP-β, 38 ΔNp63α, 39,40 PRAK, 41 PPARβ/δ, 42 and NF-κB. 43 It is not surprising that multiple regulatory pathways are involved as essential factors in the struggle between proliferation and senescence in keratinocytes transformed by oncogenic RAS since this struggle is a critical protective response in tumor formation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its key function in pro-inflammatory cytokine secretion, C/EBP- has a role in DNA damage resolution since it regulates the transcription of genes involved in DNA repair, such as BRCA1/2, ATM or Rad51 [54][55][56]. Importantly, IKK also plays a role in protecting cells from DNA-damage-induced cell death [57].…”
Section: Discussionmentioning
confidence: 99%